Delayed presentation of congenital intrinsic duodenal obstruction in children with non-bilious vomiting: a diagnostic dilemma - Kamal Nain Rattan; Jasbir Singh; Poonam Dalal (Hygeia Press di Corridori Marinella, 2018)
The duodenum is described as the most common site of intestinal obstruction, classically presenting with bilious vomiting. Of the various categories described, congenital duodenal webs are reported as a rare cause of duodenal obstruction. The clinical features may vary depending on the size and location of the duodenal web. We are reporting 5 pediatric patients with delayed presentation of congenital intrinsic (type 1) duodenal obstruction. All patients presented with recurrent non-bilious vomiting and were misdiagnosed as gastroenteritis in other centers. The diagnosis was confirmed with upper gastrointestinal tract contrast studies. The patients were managed successfully with surgical intervention.